CLASS POINT IN ACTION: ENHANCING THE STUDENTS’ VOCABULARY THROUGH INTERACTIVE LEARNING - Kesya, Kesya; Pongsapan, Nehru; Girik Allo, Markus Deli; Rum, Eka Prabawati (Teaching English as a Foreign Language Overseas Journal, 2025)
This study investigates the effectiveness of using Class Point, an interactive digital learning tool, in enhancing the vocabulary mastery of tenth-grade students at SMA Negeri 5 Tana Toraja. The research employed a quantitative method with a quasi-experimental design, involving one group of 36 students selected through cluster sampling. The research instrument consisted of a vocabulary test forming 60 multiple-choice questions, divided equally between a pre-test and a post-test. The study was conducted over ten meetings, where Class Point was used during the second to ninth sessions to deliver vocabulary instruction through interactive features such as live quizzes and instant feedback. The findings revealed a significant improvement in students’ vocabulary mastery after the implementation of Class Point. The mean score increased from 69.11 in the pre-test to 82.42 in the post-test. Statistical analysis using a paired sample t-test showed that the t-count value (7.485) exceeded the t-table value (2.03011), showing a statistically significant difference in performance before and after treatment. The results also proved higher levels of student engagement and motivation during the learning process. The study concludes that Class Point is an effective and engaging tool for improving vocabulary acquisition in English language learning. It is recommended for English teachers seeking innovative approaches to enhance student interaction and learning outcomes in the classroom.